Kuy Murojaah and Ngafal Ngefeel Communities: A Phenomenological Study of The Quran Community among Generation Z - Yudelnilastia Yudelnilastia; Widia Agustin (Pascasarjana UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
In the midst of the increasingly massive flow of digitalization, Generation Z is showing a new way of caring for spirituality and building a religious community. This research explores in depth the spiritual and social experiences of members of the digital Qur'an community such as Kuy Murojaah and Ngafal Ngefeel, who grow and develop through social media platforms. With a phenomenological approach within the framework of qualitative research, this study traces the meaning of their involvement in murojaah activities and memorization of the Qur'an, not just as a worship routine, but as an expression of religious identity, solidarity, and creativity. The findings of the study reveal that this digital Qur'an community functions as an inclusive and transformative da'wah space, where spiritual values are packaged in a relatable, aesthetic, and emotionally resonant narrative. Religious activities that were once private are now performative and communal, forming a dynamic and contextual religious ecosystem. Generation Z is not only a consumer of da'wah content, but also a producer of meaning that reshapes the relationship between technology, faith, and self-expression. Furthermore, this community becomes a social laboratory where fluid but rooted religious identity negotiations take place, where Qur'anic values are internalized through creative and participatory digital practices. This study recommends strengthening the digital da'wah approach based on experience and affection, as well as the development of a religious curriculum that is able to bridge classical spirituality with the dynamics of contemporary digital culture. Di tengah arus digitalisasi yang kian masif, Generasi Z menunjukkan cara baru dalam merawat spiritualitas dan membangun komunitas religius. Penelitian ini mengeksplorasi secara mendalam pengalaman spiritual dan sosial anggota komunitas Qur’an digital seperti Kuy Murojaah dan Ngafal Ngefeel, yang tumbuh dan berkembang melalui platform media sosial. Dengan pendekatan fenomenologis dalam kerangka penelitian kualitatif, studi ini menelusuri makna keterlibatan mereka dalam aktivitas murojaah dan hafalan Al-Qur’an, bukan sekadar sebagai rutinitas ibadah, melainkan sebagai ekspresi identitas, solidaritas, dan kreativitas religius.Temuan penelitian mengungkap bahwa komunitas Qur’an digital ini berfungsi sebagai ruang dakwah yang inklusif dan transformatif, di mana nilai-nilai spiritual dikemas dalam narasi yang relatable, estetik, dan penuh resonansi emosional. Aktivitas keagamaan yang dahulu bersifat privat kini menjadi performatif dan komunal, membentuk ekosistem religius yang dinamis dan kontekstual. Generasi Z tidak hanya menjadi konsumen konten dakwah, tetapi juga produsen makna yang membentuk ulang relasi antara teknologi, iman, dan ekspresi diri. Lebih jauh, komunitas ini menjadi laboratorium sosial tempat berlangsungnya negosiasi identitas religius yang cair namun berakar, di mana nilai-nilai Qur’ani diinternalisasi melalui praktik digital yang kreatif dan partisipatif. Studi ini merekomendasikan penguatan pendekatan dakwah digital yang berbasis pengalaman dan afeksi, serta pengembangan kurikulum keagamaan yang mampu menjembatani spiritualitas klasik dengan dinamika budaya digital kontemporer.